EXPERIENCE STUDY: EFFECT OF UNDERWRITING METHODS ON MORTALITY RATE FOR LIFE INSURANCE PRODUCT AT PT. ABC (2015-2020 PERIOD) - Imani, Alvira Adya; Hikmah, Yulial (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
In creating complex mortality tables, some insurance companies do not have enough data to build credible tables based on their experiences. Therefore, insurance companies usually carry out their analysis by comparing the company's actual mortality rate with the expected mortality rate based on industry tables, which is the "A/E ratio". This study aims to determine the best estimates for the mortality rate in PT ABC's underwriting method and its effect on the mortality rate and gross premium. The method used is the actual to expected analysis (A/E Ratio) method. The results of the research and analysis conclude that the more complex the underwriting process assigned to a product, the lower the mortality rate and gross premium.